Chitosan mitigates water stress in cowpea plants through modulation of growth, homeostasis, and antioxidant activities - Alencar, Rayanne Silva de; Viana, Priscylla Marques de Oliveira; Dias, Guilherme Felix; Bonou, Semako Ibrahim; Ribeiro, Leticia Diniz; Lourenço de Araujo, Yngrid Mikhaelly; Cavalcante, Igor Eneas; Almeida, Hermes Alves de; Viégas, Pedro Roberto Almeida; Melo, Alberto Soares de (Frontiers in Plant Science, 2025)
IntroductionClimate change and population growth increase food demand, especially in semi-arid regions. Water deficit affects cowpea productivity, but foliar application of chitosan can improve its tolerance, stimulating antioxidant activity and growth. This study analyzed chitosan application in cowpea (cv. BRS Olhonegro) under different irrigation levels, seeking alternatives to enhance productivity.MethodsThe experiment was conducted in a growth chamber using a completely randomized design. Three concentrations of chitosan (0, 50, and 75 mg L-1) were tested at varying irrigation depths (W100: 100% and W50: 50% replacement of plants evapotranspiration). At phenological stages V5 and V7, several assessments were carried out, including water status and membrane damage evaluation, leaf pigment analysis, enzymatic and non-enzymatic antioxidant activity measurement, growth evaluation, and water use efficiency determination.ResultsAt the V5 development stage, the 50 mg L-1 concentration positively influenced the relative water content, superoxide dismutase enzyme activity, proline content and total shoot dry mass. In addition, it reduced intracellular electrolyte leakage. At the V7 stage, a 75 mg L-1 concentration was particularly effective in reducing the impact of water restriction, mainly by increasing the activity of ascorbate peroxidase, proline and chlorophyll in the BRS Olhonegro cultivar.DiscussionIn summary, chitosan application mitigated the adverse effects of water stress in cowpea by maintaining water balance, preserving photosynthetic pigments, enhancing antioxidant mechanisms, and providing osmoprotection to the crop. This study highlights chitosan's potential as a cost-effective and environmentally friendly strategy to increase cowpea resilience to drought, an essential crop for food security in semi-arid regions.